Outcomes of an acceptance and commitment therapy-based skills training group for students with high-functioning autism spectrum disorder: A quasi-experimental pilot study. (November 2014) - Pahnke, Johan; Lundgren, Tobias; Hursti, Timo; Hirvikoski, Tatja
Autism spectrum disorder is characterized by social impairments and behavioural inflexibility. In this pilot study, the feasibility and outcomes of a 6-week acceptance and commitment therapy-based skills training group were evaluated in a special school setting using a quasi-experimental design (acceptance and commitment therapy/school classes as usual). A total of 28 high-functioning students with autism spectrum disorder (aged 13–21 years) were assessed using self- and teacher-ratings at pre- and post-assessment and 2-month follow-up. All participants completed the skills training, and treatment satisfaction was high. Levels of stress, hyperactivity and emotional distress were reduced in the treatment group. The acceptance and commitment therapy group also reported increased prosocial behaviour. These changes were stable or further improved at the 2-month follow-up. Larger studies are needed to further evaluate the benefits of acceptance and commitment therapy for autism spectrum disorder.